2004
DOI: 10.1016/j.jasms.2004.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Delineating mechanisms of dissociation for isomeric heparin disaccharides using isotope labeling and ion trap tandem mass spectrometry

Abstract: Heparin and heparan sulfate (HS) glycosaminoglycans have been identified as important players in many physiological as well as pathophysiological settings. A better understanding of the biosynthesis and structure of these molecules is critical for further elucidation of their biological function. We have demonstrated the successful use of negative electrospray ionization tandem mass spectrometry in the differentiation of all twelve standard heparinbuilding blocks, including the potentially important N-unsubsti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
90
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(107 citation statements)
references
References 24 publications
16
90
1
Order By: Relevance
“…They are similar to those previously reported by Saad and Leary [25]. Figures 3b, 4b, and 5b provide their corresponding CID spectra.…”
Section: Resultssupporting
confidence: 88%
“…They are similar to those previously reported by Saad and Leary [25]. Figures 3b, 4b, and 5b provide their corresponding CID spectra.…”
Section: Resultssupporting
confidence: 88%
“…Ϫ ions with higher relative intensities than did G4S-AOH (3) and G3S-AOH (8), which can also explain the lower relative abundance of [M-Na] Ϫ for those oligosaccharides that had greater intensities for loss of sulfate (see Table 2). Despite this fact, the glycosidic cleavage observations are consistent with the previously proposed [20] sulfate-mediated hydrogen transfer for B 1 formation; we then concluded that this mechanism justifies the observation that the two oligosaccharides having the sulfate group spatially closer to the glycosidic linkage, G2S-AOH (6) and G6S-AOH (7), undergo an easier B 1 fragmentation. This supposition is also supported by glycosidic fragmentation patterns found for G4S-A-G4S-AOH (4) and G4S-A-G4S-A-G4S-AOH (5).…”
Section: Patterns For G4s-a-g4s-aoh 4(a) and G-a2s-g-aoh2s 2(b) Nesupporting
confidence: 89%
“…To elucidate the origin of these fragment ions, we first attempted to establish the probable structure of the precursor B 1 ion. Along with glycosidic bond cleavage, previously general B-type cleavage mechanisms propose: (a) epoxide formation [56]; (b) double bond formation (between C-1 and C-2) with ring opening [20], and (c) double bond formation without ring opening [56]. The B 1 formation mechanism that better explains most of our results corresponds to (c) as shown in Scheme 1 [56].…”
Section: Product Ion Mass Spectra From the B 1 Ion Of Galactose-sulfasupporting
confidence: 60%
“…The singly-charged even-electron products that arise from direct fragmentation of the doublycharged negative ion can be identified by using IRMPD or CAD for ion activation, as their ions are produced by dissociation of an even-electron precursor. IRMPD of 1 produces°the°mass°spectrum°shown°in°Figure°2b,°while CAD°of°1 produces°the°mass°spectrum°shown°in°Figure 1c.°The°major°fragments°in°Figure°2b°and°c°are°princi-pally from glycosidic bond cleavages (B, C, Y, and Z) and a few cross ring cleavages in the form of 0,2 A 4 and 40].°All°of°the°fragments°observed°in°the°CAD°spectrum are found in the IRMPD spectrum, and all the IRMPD products°are°present°in°the°EDD°spectrum°(Figure°2, insets). We have found this to be generally true for all of the GAG tetrasaccharides examined to date, i.e., EDD gives the most comprehensive set of fragment ions, while the IRMPD products are a subset of the ions in the EDD spectrum, and the CAD products are a subset of the ions in the IRMPD spectrum.…”
Section: Resultsmentioning
confidence: 99%